2005
DOI: 10.1097/01.ogx.0000163875.55186.80
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Obesity, Gestational Diabetes, and Central Nervous System Birth Defects

Abstract: Several large-scale cohort studies suggest that obese mothers are at increased risk of having infants with neural tube defects and, possibly, other central nervous system (CNS) birth defects. Because obesity and diabetes share similar metabolic abnormalities, a study was planned to determine whether gestational diabetes influences the association between maternal obesity and CNS birth defects. In this population-based case-control study, covering the years 1997 to mid-2000, structured telephone interviews were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
83
3
7

Year Published

2007
2007
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(98 citation statements)
references
References 0 publications
5
83
3
7
Order By: Relevance
“…Apart from these complications are the technical problems associated with managing obese pregnant mothers during antenatal care as a consequence of reduced ultrasound accuracy, requirement of larger cuff to measure blood pressure and difficulty posed during external electronic foetal monitoring. 14 Prior studies have also found neonatal complications such as stillbirths 15,16 , congenital anomalies 17,18 and macrosomia 6 as well as gynecological problems like risk of breast cancer 19 and endometrial cancer 20 to be due to obesity.…”
mentioning
confidence: 99%
“…Apart from these complications are the technical problems associated with managing obese pregnant mothers during antenatal care as a consequence of reduced ultrasound accuracy, requirement of larger cuff to measure blood pressure and difficulty posed during external electronic foetal monitoring. 14 Prior studies have also found neonatal complications such as stillbirths 15,16 , congenital anomalies 17,18 and macrosomia 6 as well as gynecological problems like risk of breast cancer 19 and endometrial cancer 20 to be due to obesity.…”
mentioning
confidence: 99%
“…A taxa de malformações fetais é maior em mulheres obesas do que naquelas com peso normal [22][23][24][25] . O excesso de tecido adiposo parece interferir no metabolismo dos folatos, o que explicaria a maior incidência de defeitos do tubo neural entre as obesas, mesmo naquelas que recebem suplementação de ácido fólico nas doses recomendadas 22,24,26 . O risco de óbito fetal é também significativamente maior entre as mulheres com peso acima da média, por motivos ainda desconhecidos 27 .…”
Section: Repercussões Da Obesidade Sobre O Conceptounclassified
“…Multiple studies link maternal diabetes with an increased risk of congenital malformations, including anomalies of the cardiovascular, skeletal, central nervous, and urinary systems (Becerra et al, 1990;Ramos-Arroyo et al, 1992;Anderson et al, 2005;Neilson et al, 2005;Correa et al, 2008;Banhidy et al, 2010). Despite the observed association between maternal diabetes and major congenital defects, few studies have evaluated the relationship between renal agenesis/dysgenesis and maternal diabetes (Ramos-Arroyo et al, 1992;Parikh et al, 2002;Neilson et al, 2005;Correa et al, 2008;Banhidy et al, 2010).…”
Section: Introductionmentioning
confidence: 97%